The impact of perceived social support on sleep quality in a sample of patients undergoing hemodialysis in Somalia - Mohamed, Nur Adam; Mohamed, Yusuf Abdirisak; Eraslan, Asir; Kose, Samet (Frontiers in Psychiatry, 2023)
Objective: The main objective of the present study is to examine the relationship between perceived social support and quality of sleep and determine the predictors of sleep quality in hemodialysis (HD) patients in a sample from Somalia. Methods: A sample of 200 patients with end-stage renal disease (ESRD) who were undergoing hemodialysis treatment approximately two to three times a week were included. All participants were administered a Sociodemographic Data Form, the Multidimensional Scale of Perceived Social Support (MSPSS), the Insomnia Severity Index (ISI), and Pittsburgh Sleep Quality Index (PSQI). Patients on HD for less than 3 months prior to the study date were excluded. Results: Of the hemodialysis patients, 200 patients, aged between 18-68 years (mean=52.29; SD=14.13) consented and participated in the study. Sixty-three subjects (31.5%) reported poor sleep quality defined as a Total PSQI score > 5. Fourty-one subjects (20.5%) reported clinically significant (moderate-to-severe) insomnia. Majority of our HD patients reported remarkably high family support, but low friends and significant others support. Poor sleep quality significantly correlated with perceived friends support and perceived total social support. While perceived family support significantly correlated with both family income and duration of chronic kidney disease (CKD), perceived friends support significantly correlated with age and family income. Hierarchical regression analyses showed that perceived family support and friends support were significant predictors of poor sleep quality. Perceived friends support was significant predictor of insomnia severity. Perceived family support was significant predictor of subjective sleep quality and sleep duration. Perceived friends support was significant predictor of subjective sleep quality, sleep duration, sleep latency, sleep disturbance, and daytime dysfunction. Family Income was significant predictor of sleep duration. Age and gender were significant predictors of sleep efficiency. Duration of CKD and duration of HD were significant predictors of sleep disturbance. Conclusions: This present study has highlighted the value of family as a principal support system in Somali culture. Understanding the impact of perceived social support on quality of sleep in HD patients will help healthcare providers and social services to focus on and improve social support systems of the patients as an integral part of their treatment.